Modiolus phaseolinus Philippi 1844 - Ockelmann, Kurt W.; Cedhagen, Tomas (Zenodo, 2019)
Modiolus phaseolinus Philippi, 1844 NORWAY • North Sea; 58°12′ N, 4° E; 63 fathoms depth; NHMD • Skagerrak, Thor stn 35; 58º00′ N, 10°49′ E; 200 m depth; 11 Jul. 1907; NHMD • Stavanger, Lysefjord; 70–80 m depth; 17 Mar. 1902; C.M. Steenberg leg.; NHMD. SWEDEN • Bohuslän, Koster area; 1866; on the Lophelia pertusa reef; NHMD • Bohuslän; A.W. Malm leg.; NHMD. Published as part of Ockelmann, Kurt W. & Cedhagen, Tomas, 2019, Modiolus cimbricus sp. nov. (Bivalvia: Mytilidae) endemic in the Kattegat-Skagerrak, pp. 1-13 in European Journal of Taxonomy 556 on page 2, DOI:10.5852/ejt.2019.556, http://zenodo.org/record/3475433